Spontaneous Bacterial Peritonitis as a Precipitating Factor of Hepatic Encephalopathy and Its Outcomes During Hospital Admission - Mahdi, Muntazir; Ahmad, Maqsood (Indus Journal of Bioscience Research, 2025)
Introduction: Hepatic encephalopathy (HE) is a well-recognized clinical complication of liver cirrhosis and the presence and prompt identification of well-defined precipitating factors are extremely important in the diagnosis and treatment of this fatal condition. HE develops in 50% to 70% of patients with cirrhosis, and its occurrence is a poor prognostic indicator. Objectives: To determine the outcome (in terms of complete reversal of HE) of hepatic encephalopathy patients with Spontaneous bacterial peritonitis (SBP). Materials & Methods: 126 patients of hepatic encephalopathy and ascites with spontaneous bacterial peritonitis of age 20-60 years of either gender were enrolled. Patients with fulminant hepatic failure, non-cirrhotic portal hypertension, uremic, anoxic, cerebral and metabolic encephalopathy were excluded. All patients underwent standard management during their hospital stay. All the patients were assessed with these criteria and on daily basis for noting an improvement/deterioration in HE grades. Improvement of HE was defined as complete reversal of clinical symptoms on the basis of the West Haven criteria Patients with HE of ≥ grade 1 on discharge was considered as no improvement. Results: The study’s age range was 20 to 60 years old, with a mean age of 42.15 ± 9.87 years. Majority of patients i.e. 62.70%, were between 41-60 years of age. Of these 126 patients, 65 (51.59%) were males and 61 (58.41%) were females with male to female ratio of 1.1:1. Mean duration of cirrhosis was 3.51 ± 1.16 years. Improved outcome (in terms of complete reversal of HE) of hepatic encephalopathy patients with Spontaneous bacterial peritonitis (SBP) was found in 111 (88.10%) patients. Conclusion: According to the study’s findings, successful clinical outcomes can result from the early detection of hepatic encephalopathy’s precipitant variables and subsequent care.